2021
DOI: 10.14740/jmc3716
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Disseminated Nocardiosis in a Patient With COVID-19 Pneumonia

Abstract: Signs and symptoms of atypical pneumonia include fever, shortness of breath, cough, and chest pain. During the coronavirus disease 2019 (COVID-19) pandemic, identifying other causes of febrile respiratory illness in patients who tested positive for COVID-19 has been very challenging. Concerns over infecting healthcare personnel and other patients can impede further evaluations like bronchial lavage, lung biopsies, and other invasive tests. A very high index of suspicion, perhaps unreasonably so, is required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Systemic nocardiosis superimposed on COVID-19 has been previously described in a diabetic patient ( 19 ). To our knowledge, this is the first reported case of primary cerebral nocardiosis in a patient with persistent SARS-CoV-2 infection and SLE.…”
Section: Discussionmentioning
confidence: 89%
“…Systemic nocardiosis superimposed on COVID-19 has been previously described in a diabetic patient ( 19 ). To our knowledge, this is the first reported case of primary cerebral nocardiosis in a patient with persistent SARS-CoV-2 infection and SLE.…”
Section: Discussionmentioning
confidence: 89%
“…Only four other reports of nocardiosis associated with COVID-19 have been reported to date. The first case occurred in a 63-year-old man who presented with dyspnea several days after severe COVID-19 treated using dexamethasone and remdesivir [ 2 ] . In this case, pulmonary and neurological nocardiosis was diagnosed but due to preexisting lesions, the nocardiosis was thought to be present prior to the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of secondary bacterial pneumonia infections in COVID-19 has been estimated to be around 16% with gram-negative bacteria ( Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Stenotrophomonas maltophilia among others) or with gram-positive bacteria (mainly Staphylococcus aureus ), less frequently (6%) with fungi ( Aspergillus spp or Fusarium spp), and rarely with other opportunistic pathogens such as Pneumocystis jirovecii [ 1 ] . Despite extensive use of steroids and other immunosuppressive drugs in COVID-19 treatment, four cases of nocardiosis during COVID-19 have been reported [ 2 5 ] , of which two cases were suspected to be present before COVID-19 infection. We describe a case of pulmonary nocardiosis following critical COVID-19 pneumonia in an 83-year-old male suffering from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…An English literature review showed only other five reports of these associations. Data regarding these cases are shown [6][7][8][9][10].…”
mentioning
confidence: 99%